Flow and heat transfer at a nonlinearly shrinking porous sheet: the case of asymptotically large power-law shrinking rates - Prasad, Kerehalli Vinayaka; Vajravelu, Kuppalapalle; Pop, I. (Zielona Góra: Uniwersytet Zielonogórski)
The boundary layer flow and heat transfer of a viscous fluid over a nonlinear permeable shrinking sheet in a thermally stratified environment is considered. The sheet is assumed to shrink in its own plane with an arbitrary power-law velocity proportional to the distance from the stagnation point. The governing differential equations are first transformed into ordinary differential equations by introducing a new similarity transformation. This is different from the transform commonly used in the literature in that it permits numerical solutions even for asymptotically large values of the power-law index, m.
Keywords: boundary layer flow; porous shrinking sheet; Keller-Box method; similarity solutions; heat transfer